GIS ASET PEMERINTAH DI PROVINSI SUMATERA SELATAN (Studi Kasus Aset Pemerintah Kabupaten Prabumulih) - Irwansyah Irwansyah; Akhmad Khudri (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
Geographic Information System Asset mapping will provide convenience and several advantages at once in terms of: all attributes of recorded assets data and inventory in detail, achieving orderly administration of asset recording (additions, deletions, up-dating and others), data processing Asset quickly, so that information can be obtained more effectively and efficiently, providing convenience (supporting tools) in the decision-making process because it is built on the spatial concept. The problems that arise with so many local governments located in the province of South Sumatra is planning the utilization of assets that have not been optimal because the assets owned by the government of South Sumatra Province are numerous and spread geographically in several regions of the Regency and City. The solution of the problems raised is by utilizing for mapping the assets of the region. The method in this research using descriptive method and Spiral Model as system development method.